Structure of actomyosin rigour complex at 5.2 Å resolution and insights into the ATPase cycle mechanism - Takashi Fujii (Nature Portfolio, 2017)
The cyclic association and dissociation of myosin with actin filament is regulated by ATP binding and hydrolysis cycles. Here the authors report the structure of mammalian skeletal muscle actomyosin rigour complex that provides insights into the ATPase-coupled reaction cycle of actomyosin.